Mapping Islamic Bank Governance studies: a systematic literature review - Idah Zuhroh (Cogent Business & Management, 2022)
The purpose of this study is to explain the development of scientific publications on Islamic banking based on year, country, authors, and fields of science that are focused on mapping topics. This study used a qualitative method to review 696 articles published in Scopus indexed scientific journals and the collection of data was carried out in stages. Furthermore, this study reveals that the development of scientific publications on Islamic banking in the last ten years has shown an increase in the number of article because it increases yearly. However, it is both the Muslim majority and the Muslim minority countries that focus on the issue of Islamic banking. Also, the articles have clustering authors that have the same focus but discussed it with different issues. There are three important issues in the study of Islamic banking and they include the governance, auditing and supervision, and problems of Islamic banking. Also, there are dominant and other topics that are frequently discussed and have not been discussed by authors, respectively. The result showed that the sustainability of Islamic Bank Governance is for the benefit of concept development and Islamic banking practices. The limitation of this study is that it used only a qualitative method to review articles from scientific journals indexed by Scopus. Therefore, the next study needs to use scientific articles sourced from journals, books, and proceedings indexed by Scopus and Web of Science (WoS).
Keywords: 650; auditing and supervision; Islamic Bank Governance; Islamic banking; Islamic banking governance; Islamic banking problems; Islamic banking studies topics